The stricto sensu graduate program in physical education in Rio de Janeiro: A foucault’s genelogical analysis (Research, Society and Development, 2021)
The biologic conception of Physical Education is the restricted concept between health and biology, which is perpetuated for a long time in the area to account for the status quo.   This article aims to investigate the representativeness of the physical education sub-areas within the stricto sensu graduate courses in Rio de Janeiro and to discuss the effects of this distribution on the constitution of the field, based on Foucault’s genealogical analysis. For this purpose, a survey was carried out in the three stricto-sensu graduate programs in Rio de Janeiro, which sought to collect data on the four-year period (2017-2020), number of teachers, dissertations and theses defended or in progress during this period. It is concluded that given the Foucault’s genealogy in which the knowledge-power in the discursivity of the biologization of Physical Education allows us to understand that Physical Education approaches the hegemonic model of science, achieving greater legitimacy in the scientific and social fields.